Metabolic changes in kidney stone disease - Xu, Zhenzhen; Yao, Xiangyang; Duan, Chen; Liu, Haoran; Xu, Hua (Frontiers in Immunology, 2023)
Kidney stone disease (KSD) is one of the earliest medical diseases known, but the mechanism of its formation and metabolic changes remain unclear. The formation of kidney stones is a long and complicated process that is regulated by metabolic changes in various substances. In this manuscript, we summarize the progress of research on metabolic changes in kidney stone disease and discuss the role of some new potential targets. We also review the influence of metabolism of some common substances on stone formation, such as metabolic changes of oxalate, metabolic changes of reactive oxygen species (ROS), macrophage function and polarization, the role of hormones, and metabolic changes of some other substances. New insights into changes in substance metabolism in kidney stone disease, as well as emerging research techniques, will provide new directions in the treatment of stones. Reviewing the great progress that has been made in this field will help to explore new metabolic changes in kidney stone disease and also help to improve the understanding by urologists, nephrologists, and health care providers of the metabolic changes in kidney stone disease.